4,5-Diphenyl-1H-imidazole-1-acetic acid - Gao, S.; Ng, S.W.; Zain, Sharifuddin Md; Gao, J.S.; Huo, L.H.; Zhao, H. (International Union of Crystallography, 2004)
In the crystal structure of the title compound, C 17H 14N 2O 2, the 4-phenyl ring is twisted by 24.4 (3)° and the 5-phenyl ring by 72.6 (2)° with respect to the imidazole ring. Four adjacent molecules are linked by short O-H⋯N [O⋯N = 2.602 (6) Å] interactions into a hydrogen-bonded tetrameric entity. The tetramers are stacked over each other along the short c axis [5.663 (3) Å]. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.